1995
DOI: 10.1113/jphysiol.1995.sp020943
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium and force in single mouse muscle fibres following repeated contractions with stretch.

Abstract: 1. The role of the myoplasmic free Ca2+ concentration ([Ca2+]1) in the reduction of muscle force following contractions with stretch was investigated in single fibres from mouse toe muscle.Muscle fibres were either stretched by 25% of their optimum length (Lo) for ten tetani (Protocol I) or stretched by 50% of L. for between ten and thirty tetani (Protocol II). Hough (1902) recognized the condition of exercise-induced muscle damage which followed prolonged and unaccustomed exercise and was characterized by mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
181
3
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(208 citation statements)
references
References 27 publications
19
181
3
5
Order By: Relevance
“…The heightened susceptibility to damage observed here, coupled with an impaired ability to recover from injury or adapt to repeated exercise reported by others (Dedrick and Clarkson 1990;McBride et al 1995;Brooks and Faulkner 1990;Rader and Faulkner 2006;Lavender and Nosaka 2006b;Cutlip et al 2006) could be a contributor to the reduced lower limb muscle strength of elderly adults. Because contraction-induced damage impairs excitation-contraction coupling and cross-bridge function (Balnave and Allen 1995;Warren et al 1994), a heightened susceptibility to injury could initiate the age-related deterioration in muscle fiber activation and contractility (Delbono et al 1995;Wang et al 2002;Larsson et al 1997;Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001). Consistent with our results, studies conducted on skinned fibers from EDL muscles of young and old laboratory rodents have identified age-related deficits at the level of the force-producing or force-transmitting components of the cell (Lynch et al 2008;Brooks and Faulkner 1996).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The heightened susceptibility to damage observed here, coupled with an impaired ability to recover from injury or adapt to repeated exercise reported by others (Dedrick and Clarkson 1990;McBride et al 1995;Brooks and Faulkner 1990;Rader and Faulkner 2006;Lavender and Nosaka 2006b;Cutlip et al 2006) could be a contributor to the reduced lower limb muscle strength of elderly adults. Because contraction-induced damage impairs excitation-contraction coupling and cross-bridge function (Balnave and Allen 1995;Warren et al 1994), a heightened susceptibility to injury could initiate the age-related deterioration in muscle fiber activation and contractility (Delbono et al 1995;Wang et al 2002;Larsson et al 1997;Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001). Consistent with our results, studies conducted on skinned fibers from EDL muscles of young and old laboratory rodents have identified age-related deficits at the level of the force-producing or force-transmitting components of the cell (Lynch et al 2008;Brooks and Faulkner 1996).…”
Section: Discussionsupporting
confidence: 86%
“…Because contraction-induced injury to the muscle tissue has been proposed to originate at the level of the sarcomere (Proske and Morgan 2001;Morgan 1990), the present approach reveals novel information about how the injury process is initiated in different populations of muscle cells from elderly adults. A potential limitation of our chemically skinned fiber preparation is that it bypasses mechanisms of cell activation that are known to be sensitive to eccentric contractile activity (Warren et al 1993;Balnave and Allen 1995;Ingalls et al 1998), eliminates the role of extracellular ion influx on the damage process (Zhang et al 2008), and may remove strain-sensitive membrane-imbedded proteins involved in transmission of force across the sarcolemma to the extracellular matrix (Lovering and De Deyne 2004). Additional caution must be exercised when generalizing the present findings to the responses of fibers in intact organisms.…”
Section: Discussionmentioning
confidence: 99%
“…23 The findings of Warren et al 23 were confirmed and expanded upon in two studies by Balnave and colleagues. 2,3 Using the single-fiber preparation previously described, these researchers were the first to show that muscle fiber [Ca 2+ ] i during tetanic stimulation was depressed following performance of eccentric contractions. In muscle fibers losing a moderate amount of their strength (28%), the [Ca 2+ ] i during tetanic stimulation could be returned to normal by adding low levels of caffeine to the media bathing the fibers.…”
Section: Failure To Activate Intact Force-generating Structuresmentioning
confidence: 99%
“…A decrease in affinity and sensitivity of active sites of actin to Ca 2+ , the pumping rate of Ca 2+ into the sarcoplasm toward the active actin sites, and the Ca 2+ ATPase system activity has been linked to mechanisms of fatigue. Moreover, it has been pointed out as the probable cause of the mechanism of SCD and reduced muscle passive tension (55,56,57,58,59,60,61,62).…”
Section: Theory Of Non-uniformity and Instability Of Sarcomerementioning
confidence: 99%